Efektivitas Ekstrak Daun Kelor Merah sebagai Usaha Preventif terhadap Perkembangan Sel B (SDF-1) dan Sel Granulosit (Gr-1) pada Mencit Balb/c yang diinjeksi Salmonella typhi - Maria Magdalena Riyaniarti Estri Wuryandari; Hartati Tuna (Universitas Negeri Semarang, 2023)
An infection caused by Salmonella typhi can cause a reaction to DNA damage, causing a delay in the cell cycle, either temporarily or permanently, and can also cause cell death and a permanent delay in the cell cycle, causing a decrease in the self-renewal ability of haematopoetic stem cells, causing continued damage. in hematopoietic cells. Improving the immune system in the body can be done by administering synthetic drugs in the form of antibiotics or giving herbal supplements. Red Moringa has the ability as an immunostimulant and immunomodulator. The research aims to determine the effectiveness of Moringa leaf extract on the expression of B cell and granulocyte cell development due to exposure to Salmonella Typhi. The research design used experimental research using treatment groups and non-treatment groups in mice injected with salmonella typhi. Data from flow cytometry were analyzed using BD Cellquest ProTM software (%) and first transformed using arc sin transformation. The arc sin transformation results were analyzed using one-way ¬ANOVA at a confidence level of 95% (α=0.05). Data are presented in the form of mean ± standard error (SE). The results of this research, the Moringa leaf extract dose of 42mg/BW is an effective dose to restore the relative number of B cells and granulocyte cells to normal conditions.